(untitled) (Historia, 2021)
Since the inception of the SALP in 1909, conservative, reformist right-wing and militant socialist left-wing elements within the party would compromise uneasily on issues such as the colour policy and the socialist objective. Party and ideological schisms eventually took place in 1915 between pro-war and anti-war factions within the SALP on the question of Labour participation in the First World War. As a result the anti-war, left-wing militant socialist faction broke away from the SALP to form the ISL and which would eventually culminate in the formation of the CPSA in 1921. From 1915 onwards these two factions of the white labour movement would more and more diametrically and ideologically oppose one another as all efforts at reconciliation failed. This was especially the case since 1924 when the SALP became absorbed in protective and racial white labour policies, whereas the CPSA would embark on a policy to organise black labour politically and economically.